2020
DOI: 10.1111/dth.13358
|View full text |Cite
|
Sign up to set email alerts
|

Aminolevulinic acid photodynamic therapy for folliculitis decalvans: A case report

Abstract: Folliculitis decalvans (FD) is a chronic inflammatory disease with an unknown etiology. FD is characterized by chronic suppurative folliculitis, is often accompanied by pruritus or even pain, and ultimately progresses to cicatricial alopecia. Adult men have a tendency to develop this disease. The current treatments mainly consist of antibiotics, vitamin A derivatives, immune therapies, and biologics. However, some cases are intractable. Here, we present a case of recalcitrant FD that was successfully treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Two case reports reported that 3 cycles of MAL-PDT and 4 cycles of ALA-PDT resulted in sustained remission of FD for 1 year without any adjunctive therapy. 165,166 These encouraging findings were corroborated by a prospective study showing that 4 sessions of MAL-PDT resulted in a clinical response for 9/10 patients with FD, with 6 patients exhibiting disease remission, and a retrospective study showing that 9/13 patients with FD undergoing 3 sessions of ALA-PDT were well-controlled with no recurrence at 12 months. 167,168 However, the literature includes some conflicting results, with 1 case series reporting treatment failure for 3 patients with recalcitrant FD treated with a mean number of 11 MAL-PDT sessions.…”
Section: Folliculitis Decalvansmentioning
confidence: 85%
“…Two case reports reported that 3 cycles of MAL-PDT and 4 cycles of ALA-PDT resulted in sustained remission of FD for 1 year without any adjunctive therapy. 165,166 These encouraging findings were corroborated by a prospective study showing that 4 sessions of MAL-PDT resulted in a clinical response for 9/10 patients with FD, with 6 patients exhibiting disease remission, and a retrospective study showing that 9/13 patients with FD undergoing 3 sessions of ALA-PDT were well-controlled with no recurrence at 12 months. 167,168 However, the literature includes some conflicting results, with 1 case series reporting treatment failure for 3 patients with recalcitrant FD treated with a mean number of 11 MAL-PDT sessions.…”
Section: Folliculitis Decalvansmentioning
confidence: 85%
“…Photodynamic therapy demonstrated an immunemodulatory and antibacterial action, improved scar healing, anti-inflammatory properties, and can target fibroblasts, keratinocytes, sebaceous glands, and hair follicles. 8,9 Lin et al 8 reported FD stabilizing after 4 cycles of PDT at 2-week intervals. Their patient had received systemic antibiotics and isotretinoin for FD without improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al 8 have also reported the utilization of photodynamic therapy with topical aminolevulinic acid in managing a recalcitrant FD in an adult 63‐year‐old male. Photodynamic therapy demonstrated an immune‐modulatory and antibacterial action, improved scar healing, anti‐inflammatory properties, and can target fibroblasts, keratinocytes, sebaceous glands, and hair follicles 8,9 . Lin et al 8 reported FD stabilizing after 4 cycles of PDT at 2‐week intervals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic efficacy of PDT varies among different studies. Some patients experience favorable outcomes while others show no response or even worsening of symptoms [21][22][23][24].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%